Relationship between Female Sexual Dysfunction and Trunk Stability Post-Stroke: A Cross-Sectional Study - Irene del Mar Robledo-Resina; Carlos Romero-Morales; Patricia Martín-Casas; Jorge Hugo Villafañe; Vanesa Abuín-Porras (Medicina, 2024)
Background and Objectives: Stroke can lead to a variety of consequences, the severity and nature of which are contingent upon the affected brain region or lesion type. These consequences manifest with distinct clinical presentations and recovery trajectories. This study aims to investigate the potential correlation between feminine sexual dysfunction and trunk stability among stroke survivors. Materials and Methods: Thirty-eight women (stroke group n = 19 and control group n = 19) were recruited. A cross-sectional observational study was designed. Outcome measures were recorded using the Feminine Sexual Function Index, the National Institute of Health Stroke Score, the Newcastle Stroke-specific Quality of Life Measure Beck Depression Index, the Barthel Index, the Urge-urinary Distress Inventory, and the Trunk Impairment Scale. Spearman’s correlation was tested between different factors influencing feminine sexual dysfunction and trunk stability. Results: Statistically significant differences were found in sexual function between the stroke group versus the control group (Z = 88; p = 0.007; rb = 0.51). The correlation showed a relationship between feminine sexual dysfunction and trunk stability (p < 0.05). A relationship between quality of life and sexual dysfunction was also found (p < 0.05). There were no statistically significant results for the association between dependency, severity of stroke, time after stroke type of stroke, and sexual dysfunction (p = 0.378). Conclusions: The results of this study support the existence of a correlation between feminine sexual dysfunction and trunk stability, probably due to trunk and pelvic floor muscle synergy. Multidisciplinary teams assessing sexual dysfunction after stroke should include a physical therapist to assess the physical components that may interfere with feminine sexual health post-stroke.